THE APPLICATION OF THE SNOWBALL THROWING COOPERATIVE MODEL IN SCIENCE STUDIES LEARNING FOR GRADE V STUDENTS OF ELEMENTARY SCHOOL TRANS PRABUMULIH 1 - Nyai Putri Khumairo; Tio Gusti Satria; Dian Sumitra (Literasi Nusantara, 2021)
The purpose the research was to determine the completeness of the science learning outcomes of grade V Elementary school Trans Prabumulih 1 in the 2020/2021 academic year after the implementation of the snowball throwing type cooperative learning model. The research method used was the Pre-Experimental design method. The population was all grade V students of Elementary school Trans Prabumulih 1 in the academic year 2020/2021 and a sample of class V students who were determined to be 22 students who were determined by saturated sampling. The results showed that the average score of the students' test score was 32.14 with a percentage of the number of students who completed 4.54% and the final test of students was 70.26 with a percentage of the number of students who completed 81.81%. The data technique used was a 7-question essay test technique. The collected data were analyzed using the z-test. Based on the results of the z-test analysis at the significant level ? = 0.05, it was obtained z count (1.53) > z table (1.4), so it can be concluded that the results of students' science learning using cooperative learning type Snowball Throwing significantly complete.